2020
DOI: 10.15406/jamb.2020.09.00288
|View full text |Cite
|
Sign up to set email alerts
|

Macrobenthos community structure of Kan Maw Island and adjacent areas of Myeik Archipelago, Myanmar

Abstract: A study of bimonthly variations in community structure of macrobenthos in the intertidal zone was carried out in Kan Maw Island and adjacent areas of Myeik Archipelago during the low tide duration. This research was conducted at eight stations around Kan Maw Island from May 2017 to February 2019. For each station, three replicates were taken with a quadrant 30x30cm (to a depth of 30cm) along a transect and sieved with a 1mm mesh size. The macrobenthic biodiversity was represented by 73 species belonging to 42 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Ecologically, the correlation between biotic and abiotic factors is significant (Lwin et al, 2020). The present research reported the changes in population dynamics of the gastropod species that existed under the effect of the physicochemical parameter.…”
Section: Figure 5 Monthly Variations In Frequency (%) Of Studied Gast...mentioning
confidence: 67%
“…Ecologically, the correlation between biotic and abiotic factors is significant (Lwin et al, 2020). The present research reported the changes in population dynamics of the gastropod species that existed under the effect of the physicochemical parameter.…”
Section: Figure 5 Monthly Variations In Frequency (%) Of Studied Gast...mentioning
confidence: 67%
“…The presence of Polinices at station 5 is because this species likes muddy substrates. This is following Lwin (2020) which states that the dominant Polinices species are found on muddy bottom substrates. In addition, Macrophiothrix belli or snaking stars are also found at station 5 which is an area that has a muddy substrate.…”
Section: Macrobenthosmentioning
confidence: 97%